2002
DOI: 10.1037/1040-3590.14.4.451
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Multidimensional Acculturative Stress Inventory for adults of Mexican origin.

Abstract: The Multidimensional Acculturative Stress Inventory (MASI), a 36-item stress measure that was developed to assess acculturative stress among persons of Mexican origin living in the United States, was tested on a community sample of 174 adults (117 women, 57 men). Principal-components analyses yielded 4 stable and internally consistent factors: Spanish Competency Pressures (7 items), English Competency Pressures (7 items), Pressure to Acculturate (7 items), and Pressure Against Acculturation (4 items). These 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
320
4
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(337 citation statements)
references
References 30 publications
11
320
4
2
Order By: Relevance
“…The Multidimensional Acculturative Stress Inventory (MASI; Rodriguez et al, 2002) is a 36-item measure that was developed to assess stress among individuals of Mexican origin living in the United States. The MASI incorporates items that correspond to pressures from the mainstream American and Latino cultures, as well as stressors associated with developing competency in English or Spanish language.…”
Section: Acculturative Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…The Multidimensional Acculturative Stress Inventory (MASI; Rodriguez et al, 2002) is a 36-item measure that was developed to assess stress among individuals of Mexican origin living in the United States. The MASI incorporates items that correspond to pressures from the mainstream American and Latino cultures, as well as stressors associated with developing competency in English or Spanish language.…”
Section: Acculturative Stressmentioning
confidence: 99%
“…Mean scores for each subscale were calculated in which higher scores reflect greater levels of acculturative stress. Internal consistency coefficients for the MASI subscales, in the form of Cronbach's alphas, have been reported at .91, .93, .84, and .77 for English Competency, Spanish Competency, Pressure to Acculturate, and Pressure Against Acculturation, respectively (Rodriguez et al, 2002). For the present study, the coefficients were .86, .89, .86, and .73 for English Competency, Spanish Competency, Pressure to Acculturate, and Pressure Against Acculturation, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Better retention is obtained in acidic solution, whereas at higher pH values, the retention of the molecules on various soils is very weak, as reported by El Hadiri (1994). Other studies have shown the influence of the presence of metals in an ionic state in the soil on the adsorption of the pesticides (Rodriguez and Hermandez, 1985;Hance, 1969;Khan, 1974;Jamet and Piedallu, 1975;Fadayomi and Warren, 1977).…”
Section: Introductionmentioning
confidence: 99%